Failure Prediction in Laminated Fiber Reinforced Composite - ZULKIFLE, MUHAMMAD AL-AMIN (IRC, 2021)
Fiber reinforced composites are used in laminate methods. The main objective of this project is to numerically predict the failure of laminated fiber reinforced composite based on Classical Lamination Theory and Hashin Failure Criteria and compare the outcome with using Finite Element Analysis.